2018
DOI: 10.1016/j.algal.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparing EPA production and fatty acid profiles of three Phaeodactylum tricornutum strains under western Norwegian climate conditions

Abstract: Microalgae could provide a sustainable alternative to fish oil as a source for the omega-3 polyunsaturated fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). However, growing microalgae on a large-scale is still more cost-intensive than fish oil production, and outdoor productivities vary greatly with reactor type, geographic location, climate conditions and microalgae species or even strains. The diatom Phaeodactylum tricornutum has been intensively investigated for its potential in large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 41 publications
3
29
2
Order By: Relevance
“…The diatom Phaeodactylum tricornutum is photoautotrophic in nature, while it can be grown in mixotrophic conditions, allowing photoautotrophic as well as heterotrophic cultivation conditions simultaneously, although, in this case, glucose utilization requires light [158][159][160][161][162][163][164][165][166][167]. When glucose transporters were introduced through genetic engineering, P. tricornutum could grow heterotrophically on various carbon sources in the dark [166,168].…”
Section: Oleaginous Microalgae and Diatomsmentioning
confidence: 99%
“…The diatom Phaeodactylum tricornutum is photoautotrophic in nature, while it can be grown in mixotrophic conditions, allowing photoautotrophic as well as heterotrophic cultivation conditions simultaneously, although, in this case, glucose utilization requires light [158][159][160][161][162][163][164][165][166][167]. When glucose transporters were introduced through genetic engineering, P. tricornutum could grow heterotrophically on various carbon sources in the dark [166,168].…”
Section: Oleaginous Microalgae and Diatomsmentioning
confidence: 99%
“…Furthermore, our preliminary observations suggested that Pt4 appeared to have higher yields of LDs from cells disrupted by hypotonic shock, perhaps because they are more amenable to this particular cell disruption method, and potentially related to differences in membrane lipid composition (Steinrücken et al. 2018) or owing to differences in their environments of origin (Martino et al. 2007).…”
mentioning
confidence: 90%
“…Two strains of the diatom P. tricornutum and one strain of Attheya septentrionalis showed high growth rates (≥ 0.7 divisions day −1 ) and increased EPA content in laboratory scale experiments (Table ). When the two local strains of P. tricornutum were grown outdoors, in flat panel photobioreactors, during a 6 months period (May–October) they were outperformed in terms of EPA production by a commercial strain of P. tricornutum (Steinrücken et al ). Moreover, outdoor vs indoor (laboratory) cultivation had a profound effect on the fatty acid composition.…”
Section: Exploring and Exploiting The Natural Diversity Of Microalgaementioning
confidence: 99%